WordPress 2 - Langer, Maria (Visual quickstart guide., 2006)
WordPress is an open-source personal publishing platform that is easy to use, flexible, and highly customizable. Although used primarily for publishing blogs, WordPress can easily be used to create and maintain complete Web sites. Taking the average blogger further than blogspot can, WordPress allows bloggers to create more complicated sites with their open-source technology, rather than blogger which is limited by HTML changes to their templates. This easy-to-follow, step-by-step guide shows you how to install, use, and customize WordPress to get the most from the software. Includes tips that explain why certain techniques are better than others, how to watch for potential problems, and where readers can find more information.